The improvement of energy-consuming right trading policy on the efficiency of urban green development - Guo, Bingnan; Hu, Peiji; Zhang, Hao; Weng, Xiayan; Hu, Feng (Frontiers in Environmental Science, 2023)
As a measure to promote the reform of China’s ecological civilization system, the energy-consuming right trading policy have great potential to reduce pollutant emissions and achieve green development in China. Based on the panel data of 254 cities in China from 2005 to 2019, this paper uses the difference-in-differences (DID) model to investigate the impact of energy-consuming right trading policy on the efficiency of urban green development. The findings are as follows. (1) The energy-consuming right trading policy can significantly promote the efficiency of urban green development. The conclusion still holds after a series of robustness tests. (2) The energy-consuming right trading policy can improve the efficiency of urban green development by promoting green technology innovation. This finding supports the Porter Hypothesis. (3) Heterogeneity analysis shows that the energy-consuming right trading policy can significantly improve the green development efficiency of cities in the eastern region. On the contrary, there is no significant effect on the green development efficiency of cities in the central and western regions. This paper fills in the gaps of related research and provides an important reference for the improvement and development of energy-consuming right trading policy.